Comparative evaluation of magnetic stirrer and homogeniser on globules characterization and stability of red palm oil submicroemulsion prepared by d-phase emulsification method - Elsa Fitria Apriani; Tommy Julianto Bustami Effendi; Windy Keumala Budianti; Mahdi Jufri (JURNAL ILMU KEFARMASIAN INDONESIA, 2026)
Red palm oil (RPO) contains antioxidants due to its carotenoid and vitamin E content. However, the lipophilicity and instability of these two compounds may reduce RPO's bioavailability and efficacy of RPO. This study aimed to develop RPO submicroemulsions and evaluate the effects of magnetic stirrer (M) and homogeniser (H) on their characteristics and physical stability. A submicroemulsion was developed using the D-phase emulsification method. Formulas with globule sizes less than 200 nm, polydispersity index (PDI) less than 0.4, and zeta potential less than -30 mV were tested for stability at room temperature for 3 months and analysed for Ostwald ripening rates. The homogenizer method produced smaller globule sizes and lower PDI (p<0.05). Ten formulations from both the magnetic stirrer and homogeniser methods met the initial globule requirements. After 3 months, F4H and F9H showed the best physical stability with globule sizes of 181.23±0.96 and 175.23±1.88 nm, PDI of 0.077±0.034 and 0.035±0.023, and zeta potential of -33.80±0.56 and -30.57±0.15 mV (p>0.05). However, F9H had a lower Ostwald ripening rate than F4H, namely 2.54×105 and 6.04×105 nm3/month, respectively. In conclusion, the homogeniser produced more stable RPO submicroemulsions than the magnetic stirrer.